Do spatial factors outweigh institutional factors? Changes in influencing factors of home-work separation from 2007 to 2017 in Beijing. (October 2021) - Li, Chunjiang; Zhang, Yan; Chai, Yanwei
Abstract: Extensive literature has investigated the impacts of different influencing factors on home-work separation in urban China. However, most studies have adopted a cross-sectional design, which provides little direct evidence on changing trends in these effects in the context of rapid urban transformation. This study examined the 10-year changes in the factors influencing home-work separation in Beijing. By drawing on community surveys conducted in 2007 and 2017, we constructed two regression models under the same framework, considering the implications of sociodemographic, built environment and institutional factors on home-work separation in the respective year. A t -test was employed to compare the effects of the same factors on home-work separation between the 2007 and 2017 models. We found that the relationships between the influencing factors and residential home-work separation changed substantially from 2007 to 2017, indicating dramatic urban transformations in Chinese cities. Specifically, the effects of the built environment measured by population density and jobs-to-housing ratio became stronger, reflecting the rapid urban expansion and suburbanization of Chinese cities. The effect of danwei system became weaker due to the removal of the housing provision responsibility of danwei as well as the dissolution of existing danwei. The direction of the effect of hukou changed from negative to positive because of the relaxation of the hukou system. In addition, the effects of sociodemographic attributes changed. The effects of socioeconomic attributes reflecting the market force such as income and education level became stronger, while the effects of demographic attributes related to social role such as gender and age became weaker. We further discuss the debate on institutional constraints and the legacy of danwei, the transformations in Chinese cities, and the implications for policymaking aiming to reduce home-work separation.